Direct verbal aggression in school settings: A review of the literature. (May 2019) - Poling, Daniel V.; Smith, Stephen W.; Taylor, Gregory G.; Worth, Megan R.
Abstract: Overt physical aggression in schools gains the most attention from educational professionals, yet researchers find that verbal aggression (VA) delivered directly is the most prevalent form. Perpetrators who engage in VA can experience a host of negative long-term outcomes and victims often experience anxiety, depression, and even suicide ideation. A review of the current literature about VA is essential to raise awareness of this form of aggression and to develop strategies to mollify its deleterious effects. Thus, the purpose of our review is to explore VA, specifically its prevalence and demographics, internalizing effects, and related risk and protective factors. We also examine student perspectives, school climate and safety, the relationship between academic performance and VA, and current interventions. We discuss future research, including the need to situate conceptually VA processes and cognitive events, mediators and moderators, proximal and distal outcomes of VA, and the need for efficient and effective interventions. Highlights: Verbal aggression is the most prevalent form of aggression reported by students in schools. Verbally aggressive behavior tends to peak during middle school years. Internalizing problems such as depression and anxiety are linked to verbal aggression. Few interventions exist that target verbal aggression.